Moderating Effect of Tax Avoidance on Firm Size and ROA: Study of Insurance Sector at IDX 2021-2025 Period - Nadia Putri Zahra; Iwan Sidharta (P3M, STIE Pasundan, Bandung, Indonesia., 2026)
This study examines how Tax Avoidance moderates the impact of Firm Size on financial performance, specifically Return on Assets (ROA). Utilizing a quantitative approach, the methodology analyzes secondary panel data gathered from the Indonesia Stock Exchange (IDX) spanning 2021 to 2025. The sample consists of nine insurance sector companies, yielding 45 observations over the five-year period. Following classical assumption testing to ensure unbiased estimates, the analysis applies Hayes' Conditional Process Analysis to evaluate the shifting effects of corporate scale on profitability at various levels of tax management. The findings reveal that Tax Avoidance acts as an actually weakens in this relationship. While larger firm size fails to improve ROA when tax avoidance is low or average, it significantly drives profitability upward when companies engage in high levels of tax avoidance. This provides a crucial implication for corporate managers, suggesting that large insurance firms must strategically align their organizational scale with optimized tax planning to successfully maximize financial returns. The originality of this research lies in its specific application of conditional process modeling to the Indonesian insurance sector, mapping the exact thresholds where tax planning transforms from an insignificant factor into an active catalyst for asset profitability.